Examination of species delimitation of ambiguous DNA-based Ulva (Ulvophyceae, Chlorophyta) clades by culturing and hybridisation. Issue 5 (1st September 2017) - Hiraoka, Masanori; Ichihara, Kensuke; Zhu, Wenrong; Shimada, Satoshi; Oka, Naohiro; Cui, Jianjun; Tsubaki, Shuntaro; He, Peimin
Abstract: Phylogenetic clades based on DNA sequence data are heavily used to delimit species in the current taxonomy of Ulva . However, because hybridisation within clades and among other clades for other species has been seldom tested, it remains unclear if molecular clades agree with species boundaries based on the biological species concept. An ITS-based Ulva clade including many specimens collected worldwide was provisionally named ' U. flexuosa '; its species boundary is ambiguous, and in the literature this group has been variously merged with the closely related U. californica clade. In the present study, we clarified the species boundary of this clade and its taxonomic status. Namely reproductive relationships among strains in this and closely related clades were examined by culturing and hybridisation. The culture experiment demonstrated that the ITS-based clade includes a sexual variant and an obligate asexual variant. The sexual strains having 0%–0.4% divergence in ITS2 sequence successfully crossed with each other. In combinations among the closely related clades including true U. flexuosa with > 1.2% distance in the sequence, no hybridisation occurred. With U. californica strains having a 1.2% sequence divergence, the provisional ' U. flexuosa ' strains had few hybrid sporophytes, and these produced zoids that failed to develop normally. Based on these observations of prezygotic and postzygotic isolation, we conclude that the ITS-based clade delimits a different species from U. flexuosa and U. californica . Taxonomically, both the sexual and the asexual variants are assigned to U. mediterranea .